Early infantile form of galactosialidosis presenting as nonimmune hydrops fetalis: a case report - Rita Gomes; Bebiana Sousa; Cláudia Falcão Reis; Anabela Bandeira; Lurdes Morais; Sandra Pereira; Sara Leite; Carmen Carvalho (Hygeia Press di Corridori Marinella, 2022)
Case report: A 20-year-old woman was referred to our tertiary center due to hydrops fetalis (HF) diagnosed at 24 weeks of gestation. She had severe acne and underwent treatment with isotretinoin up to a month before pregnancy. The parents were consanguineous. The third trimester ultrasound revealed median volume ascites and generalized subcutaneous edema. Maternal parvovirus B19 serologies showed positive IgG and IgM antibodies. Elective caesarean section was performed at 30 weeks, demanding immediate postnatal resuscitation, including mechanical ventilation and evacuation paracentesis. The newborn had coarse facies, subcutaneous edema, marked abdominal distention, abdominal telangiectasias, mild hypertrophy of the labia minora, short long bones and fourth right toe clinodactyly. The HF next generation sequencing (NGS) gene panel identified a homozygous variant in exon 3 of the CTSA gene [NM_000308.4:c.254G>T p.(G85V)]. Biochemical lysosomal study of cultivated amniocytes confirmed the diagnosis of galactosialidosis (GS). Follow-up and palliative care by a multidisciplinary team ensued. Parental genetic testing confirmed carrier status for the aforementioned variant and further genetic counseling was provided. Discussion: Elucidation of the etiology of non-immune HF is essential for determining treatment and prognosis. Despite being extremely rare, GS is one of the most common lysosomal storage diseases. An early diagnosis allows for better care as well as genetic counseling for future pregnancies. An experienced multidisciplinary team is essential for optimal management.